POTENSI KONFLIK PADA TRADISI MERARIK DI PULAU LOMBOK - AHMAD FATHAN ANIQ (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2011)
Merarik is a marriage process of Sasak tradition in which a bridegroom runs away with the bride before marriage settlement or wedding procession is conducted lawfully based on both religion and national law. Initially, merarik is merely a term of an action running away with a girl to take in marriage. However, later on, it has a wider meaning. It is extensively used to name a whole series of marriage in Sasak community. Unfortunately, nowadays the tradition of merarik is frequently misapplied as a way to abduct a girl to be married even though without any agreement of her parents. It frequently causes conflicts between two families. In this regard, merarik becomes an interesting topic to discuss because at all events, several practices of such a tradition contravene the rights of women and their parents. Women cannot make a choice a bridefroom whom they love.Moreover, under-age marriages also often occur. As a consequence, most of women stop far schools. Why does the tradition of merarik still exist in a society This phenomenon shows as if there is a legitimation of the Sasak men who have a mind to maintain this tradition. This article tries to study how Sasak community as the majority of Muslim understand and interprete this phenomenon. Key Words: Merarik, Marriage, women forcefulness, Sasak Community